Different but complementary roles of action and gaze in action observation priming: Insights from eye- and motion-tracking measures - Letesson, Clément; Grade, Stéphane; Edwards, Martin G. (Frontiers in Psychology, 2015)
Action priming following action observation is thought to be caused by the observed action kinematics being represented in the same brain areas as those used for action execution. But, action priming can also be explained by shared goal representations, with compatibility between observation of the agent’s gaze and the intended action of the observer. To assess the contribution of action kinematics and eye-gaze cues in the prediction of an agent’s action goal and action priming, participants observed actions where the availability of both cues was manipulated. Action observation was followed by action execution, and the congruency between the target of the agent’s and observer’s actions, and the congruency between the observed and executed action spatial location were manipulated. Eye movements were recorded during the observation phase, and the action priming was assessed using motion analysis. The results showed that the observation of gaze information influenced the observer’s prediction speed to attend to the target, and that observation of action kinematic information influenced the accuracy of these predictions. Motion analysis results showed that observed action cues alone primed both spatial incongruent and object congruent actions, consistent with the idea that the prime effect was driven by similarity between goals and kinematics. The observation of action and eye-gaze cues together induced a prime effect complementarily sensitive to object and spatial congruency. While observation of the agent’s action kinematics triggered an object-centered and kinematic-centered action representation, independently, the complementary observation of eye-gaze triggered a more fine-grained representation illustrating a specification of action kinematics toward the selected goal. Even though both cues differentially contributed to action priming, their complementary integration led to a more refined pattern of action priming.